IMPROVING STUDENT’S VOCABULARY ACHIEVEMENT THROUGH “MAKE A MATCH METHOD” - Ade Iriyani; Sortha Silitonga (Universitas Negeri Medan, 2013)
The objective of the study is to find out if the students’ vocabulary achievement improved through Make a Match Method. The research of this study was conducted by using action research. The subjects of this study were the second year students of MTs Swasta Al-Badar Tanjungbalai class VIII consisted of 31 students. The research was conducted in two cycles and every cycle consisted of three meetings. Quantitative and qualitative instruments were used to gather the data. Quantitative data was taken from the students’ score in vocabulary mastery, while qualitative data was taken from diary notes, observation sheets and questionnaire sheets. Based on the data, the students’ scores got improvement in every cycle. In test I, the mean of the students’ score was 59 while test II, the mean of the students’ score was 70.5 and in test III the mean of the students’ score was 77.3. It was found that the teaching vocabulary through Make a Match Method improve the students’ vocabulary Achievement. It is suggested that English teacher use Make a Match Method as one of alternatives method in teaching vocabulary.